A Cognitive Linguistic Study of Iraqi EFL University Students' Interpretations of Flash Fiction - Abdulzahra Naait, Saleema; Saaran Hmood , Shaima'a (Journal of College of Education, 2020)
This study follows the cognitive linguistics approach to analyze the Iraqi university students' interpretations of (one sentence) flash fiction. Flash fiction is a literary work characterized by its brevity, but still offers character development and plot; it has a unique literary quality. The study depends on schema theory; the model for analysing data is Fillmore’s Frame Semantics (1982).The students’ interpretations of one sentence flash fiction are the data for this study; the data are collected by a reflection test and semi-structured interview. The theory of frame semantics relates linguistic meaning to encyclopedic background knowledge and previous experience. The study at hand aims at examining the role of evocation in highlighting invocation among the participants in the selected one-sentence stories, determining the words that evoke these reflections, and investigating the gender-based differences and similarities regarding the number of evocations identified with the possible invocation associated to them. The study clarifies that the different schema (previous knowledge and experience) of the students create different interpretations for such brief and rich sentences of flash fiction, in spite of the fact that they have the same educational background and about the same age. However, and due to their shared cultural knowledge, there is some sort of similarity in their interpretations. Moreover, approximately in all interpretations, specific words worked as the keys for interpreting the text under investigation and these words activated different frames. It has been concluded that difference in gender has no impact on the students' interpretations of short story sentences, which enhances the idea that meaning is conceptual and is individual proper.